2004
DOI: 10.1073/pnas.0308698100
|View full text |Cite
|
Sign up to set email alerts
|

Short interfering RNAs can induce unexpected and divergent changes in the levels of untargeted proteins in mammalian cells

Abstract: RNA interference (RNAi) mediated by short interfering RNAs (siRNAs) is a widely used method to analyze gene function. To useRNAi knockdown accurately to infer gene function, it is essential to determine the specificity of siRNA-mediated RNAi. We have assessed the specificity of 10 different siRNAs corresponding to the MEN1 gene by examining the expression of two additional genes, TP53 (p53) and CDKN1A (p21), which are considered functionally unrelated to menin but are sensitive markers of cell state. MEN1 RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
372
4
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(394 citation statements)
references
References 29 publications
15
372
4
3
Order By: Relevance
“…Some nonspecific effects of siRNA at high concentrations were also observed for L2000-delivered control siRNA and have been described by others. 37,38 Results obtained with BHK21 cells were very similar to those shown for MDCK cells in Figure 8 (not shown).…”
Section: Delivery Of Sirna To Cultured Cellssupporting
confidence: 76%
“…Some nonspecific effects of siRNA at high concentrations were also observed for L2000-delivered control siRNA and have been described by others. 37,38 Results obtained with BHK21 cells were very similar to those shown for MDCK cells in Figure 8 (not shown).…”
Section: Delivery Of Sirna To Cultured Cellssupporting
confidence: 76%
“…First, a wild type of siRNA oligo and also a corresponding mutant (control) oligo were synthesized (Figure 3a). These oligos have been previously used by other researchers to silence p53 expression in other human cells (Scacheri et al, 2004). When the two oligos were separately introduced into HLECs for 72 h, silence of p53 expression by the wildtype siRNA oligo reached a level of 88% in comparison with the mutated oligo and a similar level when compared with the nontransfected HLECs (Figure 3b).…”
Section: Resultsmentioning
confidence: 78%
“…The effects of the gastrin siRNA appear to be specific. The possibility of off-target effects (Scacheri et al, 2004) and induction of the interferon response (Sledz et al, 2003) has been suggested in the literature. A BLAST search was included in the design of the siRNAs used in this study and no matches to other genes were identified.…”
Section: Discussionmentioning
confidence: 99%